Improving Students’ Critical Thinking Skills Trough Contextual Teaching and Learning Science Module - Siti Nur Hasanah; Widha Sunarno; Baskoro Adi Prayitno (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
This study aims to determine the effectiveness of the science module based on the contextual learning approach (CTL) in improving the critical thinking skills of junior high school students. The research method used was a quasi-experimental study involving 30 students in the experimental class and 30 students in the control class from a junior high school in Surakarta. The data collection technique was done by measuring students' critical thinking skills before (pretest) and after learning using the Science module (posttest). The instrument used was a critical thinking skill test based on Facione's critical thinking skills indicator. The improvement of students 'critical thinking skills was analyzed using a pretest-posttest gain score and followed by an independent sample t-test to determine the significance of the difference in the average increase in students' critical thinking skills. The results showed that the use of a science module based on a contextual learning approach could improve students' critical thinking skills, with a score of 0.46, or in the category of moderate improvement compared to control class students, with a score of 0.29, or in the low improvement category. Meanwhile, based on the results of the t-test the average gain score of the two classes shows a significant difference in the improvement of critical thinking skills between students who are taught using the Science module and students who are taught using conventional modules.